2021
DOI: 10.1111/luts.12416
|View full text |Cite
|
Sign up to set email alerts
|

Cystectomy for patients with Hunner‐type interstitial cystitis at a tertiary referral center in Japan

Abstract: Cystectomy is an ultimate treatment option for patients with end-stage Hunner-type interstitial cystitis (HIC). However, pertinent information regarding this procedure such as optimal candidate selection, surgical procedures, possible complications, and treatment prognosis, is limited owing to its extremely low prevalence. We report outcomes of 17 cystectomies for end-stage HIC patients at a tertiary referral center in Japan over a period of 20 years, including partial cystectomy with augmentation ileocystopla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In patients who underwent total cystectomy, complications arising from ureteroileal anastomotic stricture were observed in two cases, which were managed using ureteral stent placement and nephrostomy. 46 In contrast, several studies, including ours, have indicated that subtotal cystectomy provides substantial symptom improvement and yields more favorable functional outcomes than total cystectomy. In our aforementioned study involving 40 patients with Hunner-type IC who underwent supratrigonal cystectomy with ileocystoplasty, we noted significant enhancements in frequency and nocturia, pain levels measured using the pain VAS, and improvements in ICSI and ICPI when comparing measurements taken before and after surgery.…”
Section: Which Approach Is Acceptable For Hunner-type Ic: Total or Su...mentioning
confidence: 56%
See 3 more Smart Citations
“…In patients who underwent total cystectomy, complications arising from ureteroileal anastomotic stricture were observed in two cases, which were managed using ureteral stent placement and nephrostomy. 46 In contrast, several studies, including ours, have indicated that subtotal cystectomy provides substantial symptom improvement and yields more favorable functional outcomes than total cystectomy. In our aforementioned study involving 40 patients with Hunner-type IC who underwent supratrigonal cystectomy with ileocystoplasty, we noted significant enhancements in frequency and nocturia, pain levels measured using the pain VAS, and improvements in ICSI and ICPI when comparing measurements taken before and after surgery.…”
Section: Which Approach Is Acceptable For Hunner-type Ic: Total or Su...mentioning
confidence: 56%
“…Several studies have reported significant symptom improvements after total cystectomy. 45,46 Peters et al found that of eight patients who underwent total cystectomy with an ileal conduit for Hunner-type IC, complete resolution of pain was observed in seven. Although four (50%) patients required reoperation, such as urostomy revision, six patients reported a "marked improvement" in their postoperative QoL.…”
Section: Which Approach Is Acceptable For Hunner-type Ic: Total or Su...mentioning
confidence: 99%
See 2 more Smart Citations
“… 4 However, to date, optimal patient selection and standardized surgical procedures have not been established. 5 Here we describe the first case of a young woman with HIC who underwent pelvic organ‐preserving robot‐assisted simple cystectomy and intracorporeal ileal neobladder reconstruction.…”
Section: Introductionmentioning
confidence: 99%